Bahasa Inggris - Ratri Novita Erdianti; Jessica Widya Larossa; Muhamad Helmi Md. Said; Said Noor Prasetyo (Universitas Muhammadiyah Surabaya, 2026)
Overcrowding in correctional institutions significantly affects Indonesia's correctional system. This leads to problems like decreased effectiveness, inefficient budgeting, social impacts, and human rights violations. We must urgently assess the penal system by adopting a broader view of punishment objectives. This paper evaluates the penal system's effectiveness, focusing on short-term deprivation of liberty, and examines community service as an alternative to imprisonment under criminal law reform. We use a normative juridical approach to analyze legal issues related to short-term deprivation of liberty from the viewpoint of punishment objectives. The results show that community service aligns well with punishment objectives; it provides a more effective and efficient alternative to short-term imprisonment, which often fails to deliver optimal rehabilitative and preventive effects. The novelty of community service orders lies in its role as an instrument to address the limitations of short-term imprisonment, broadening the punishment paradigm toward a more humanistic, productive, and reintegration-oriented approach.